THE TIME DELAY OF EXTRAGALACTIC COSMIC RAYS IN THE GALACTIC MAGNETIC FIELD - Elyiv, A. A.; Hnatyk, B. I. (Одеські астрономічні публікації, 2017)
We investigate the propagation of extragalactic cosmic rays (ECRs) in the regular component of the Galactic magnetic field. Especially we numerically calculate the expected time delay of ECRs due to curvature of trajectories. The maps of time delay depending on energy and arrival directions of ECRs have been constructed. We show that regular component of Galactic magnetic field increases the time delay up to 700 kyr for low-energy part (E>=3x10^17 eV) of ECRs. This value is noticeably larger than the expected time delay in a random (turbulent) component of the Galactic magnetic field. Both regular and turbulent components of Galactic magnetic field do not modify considerably ECR flux and spectrum at energy E>= 10^18 eV.